Effects of peritoneal injection of NH4HCO3 on nitrogen excretion and metabolism in the swamp eel Monopterus albus - Increased ammonia excretion with an induction of glutamine synthetase activity - Lim, C.K. (2014)
Journal of Experimental Zoology Part A: Comparative Experimental Biology